Kemampuan Metabolisme Asam Linoleat oleh Kandidat Probiotik Potensial Asal Feses Bayi Asli Indonesia - Nosa Septiana Anindita; Muslih Anwar Widodo; Tiyas Tono Taufik; Tutik Dwi Wahyuningsih (Universitas 'Aisyiyah Yogyakarta, 2018)
Six probiotic candidates were grown overnight at 37 °C in De Man Rogosa Sharpe(MRS) broth supplemented with 0.4 mg/mL of linoleic acid. The concentrations of the metabolite products in the culture media were determined using GC-MS after extraction and direct transesterification of the fatty acids. Linoleic acid was added to the sample as an internal standard. The result showed that Lactobacilluscasei strainAPwas able to convertfreelinoleicacidto conjugated linoleic acid in themedia more than 60% while five other potential probiotics such as Lactobacillus casei AF, Lactobacillus casei AG, Pediococcus acidilactici AA, Pediococcus acidilactici BE and Pediococcus acidilactici BK have abilities to convert free linoleic acid to palmitic acid, stearic acid and oleic acid with varying percentages.